IMPLEMENTATION OF TRANSPORTATION POLICIES IN THE MAINTENANCE OF PUBLIC STREET LIGHTING EQUIPMENT IN THE CITY OF SUKABUMI - Frisda Amelia Augusty; Ike Rachmawati; Tuah Nur (DIA: Jurnal Administrasi Publik, 2025)
This study aims to analyze the implementation of transportation policies in the maintenance of public street lighting (PJU) in Sukabumi City, PJU is a very important public facility to support the safety and comfort of road users at night. Therefore, PJU maintenance must be carried out optimally in accordance with applicable policies. This research used qualitative method with descriptive approach, data collection technique through field observation, interview, and documentation. Informants were determined by non-probability sampling technique and snowball sampling method. This research uses the theory of Van Meter Van Horn (1975). The results of this study indicate that the implementation of transportation administration policies in maintaining PJU in Sukabumi City is still not optimal. Such as budget constraints, lack of coordination between related institutions, and lack of community participation. However, improvement efforts continue to be made to improve the quality of PJU services in Sukabumi City.